(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was necessitated by the need to ascertain whether business education graduates acquire adequate skills for entrepreneurial success by determining small and medium enterprises managers’ ratings of such skills needed by business education graduates for entrepreneurial success in Ondo and Ekiti States. Two research questions guided the study and two hypotheses were tested. The design of the study was descriptive survey. The population for the study was 540 managers out of which 230 were sampled. A structured questionnaire having five point rating scale which was duly validated by experts in the field was used to collect data. Test re-test method was used to determine the reliability of the instrument and application of Cronbach Alpha for the internal consistency yielded an overall reliability coefficient of 0.75. Mean and standard deviation were used to analyze data in respect of research questions and to determine the cohesiveness or otherwise of respondents’ ratings. The z-test was used to test the hypotheses at 0.05 level of significance. Findings revealed that small and medium enterprises managers rated problem-solving and marketing skills as the skills highly needed by business education graduates for entrepreneurial success in the area. Based on these findings, it was recommended among othersthat government and professional body such asAssociation of Business Educators ofNigeria (ABEN)should float training programmes such as workshops, seminars and conferences on the skills needed for entrepreneurial success to build and enhance the capacity of business teachers, business education students, business education graduates, entrepreneurs and general public at regularintervals.